FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU KONSUMSI JUNK FOOD PADA SISWA SEKOLAH DASAR DI KECAMATAN SELAT NASIK KABUPATEN BELITUNG TAHUN 2023 - Juansyah, Trisna (Coping: Community of Publishing in Nursing; Vol 12 No 1 (2024): Februari 2024DO - 10.24843/coping.2024.v12.i01.p11, 2024)
Tendency to choose unhealthy foods, such as junk food , sweet or salty snacks with a high content of sugar, salt and saturated fat which can affect health so that this has an impact on the consumption behavior of elementary school students who like to eat junk food . The purpose of this research is to find out what factors are related to consumption behavior junk food in elementary school students at the Selat Nasik District, Belitung Regency in 2023. This research is a quantitative research method cross-sectional which aims to examine whether there is a relationship between knowledge, attitudes and peer influence with consumption behavior junk food in elementary school students. The sample in this study were all elementary school students in grades IV, V and VI in Selat Nasik District, Belitung Regency, totaling 123 people. Data analysis used chi square test with a degree of freedom 95%. This research concludes the factors related to consumption junk food are knowledge (p=0.028), attitude (p=0.016) and factors that are more dominant in peer influence (p=0.000 and POR=5.765). The recommendation in this study is the need for the school to cooperate with the health center to provide education on the influence of peers in comsumption junk food and it is necessary to educated parents of students to prevent consumption junk food excessively